ASSESSMENT OF TOMATO FARMERS’ IRRIGATION PRACTICE IN PAMPAIDA MILLENNIUM VILLAGE, IKARA LOCAL GOVERNMENT AREA, KADUNA STATE, NIGERIA - Ahmed, A.; Oyebode, M. A.; Igbadun, H. E.; Oiganji, E. (FUDMA JOURNAL OF SCIENCES, 2020)
This study was conducted in Pampaida Millennium Village (PMV), Ikara Local Government Area of Kaduna State, Nigeria; during the 2009/2010 dry season to assess Tomato farmerâ€™s irrigation water management practice using furrow irrigation. A total of 7 tomato farmers were selected out of 45 farmers for the assessment exercise. Soil moisture content was monitored throughout the growing season using gypsum blocks. The hydraulic performance of the farmerâ€™s plots were assessed.  Similarly, the seasonal water requirement and irrigation schedule for the irrigated tomato were also determined. The results showed that the highest Application Efficiency, Distribution Uniformity and Adequacy of irrigation were obtained in plots T6 (92%), T3 (89%) and T7 (92 %) respectively. The least AE, DU and AI were obtained in plot T1 as 74%, 72% and 63% respectively. The yield obtained ranged from 11.6t/ha to 22.3t/ha. The least yield was obtained in plot T2; while the highest yield was obtained in plot T1. All the assessed farmers maintained a 4day irrigation interval throughout the growing season. The highest crop water use efficiency (CWUE) of 62.80 kg/ha-mm was obtained in plot T1, with a corresponding crop water use (CWU) of 355 mm/season. The least CWUE was obtained in plot T2 (41.6kg/ha-mm) with a corresponding CWU of 399 mm/season. Based on the results obtained it can be deduced that plot T1 gives best results among the assessed farmersâ€™ plots in terms of crop water use efficiency and effectiveness of irrigation, which maximizes net farm profit.
Keywords: Surface irrigation, water use efficiency, performance evaluation, Application Efficiency